PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 025 TELUK BINJAI DUMAI TIMUR - Jayasni '; Hendri Marhadi Marhadi; Gustimal witri witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. The Purpose of this research is to enhance the student’s learning result of 4th grade in SDN 025 Teluk Binjai Dumai Timur 2013/2014 school year. This research carries out at 14 April 2014 with total number of students 22 that is consists of 12 male student and 10 female students. Yhe kind of this research is classroom action research. The research instrument that had been used is the students study result, students activity, and teacher activity. The research instrument that had beeb used the sheet items reserved and sheet items observation of students activity and teacher activity. The model of cooperative learning type “Think Pair Share”carries out at six times. It consists of four times plant of implementation of the learning, two times daily test, the conclusion of this research is the study results enhance in every time cycle 1 and cyle 2. The problems prove with enhance the average of study result of  IPS subject for the 1st data is 58,86, in 1st daily test enhance to 81,59, in 2nd daily test enhance to 90,91. From this research conclusion The Implementation model of cooperative learning type “Think Pair Share” can enhance the study result of IPS subject for the 4th students grade in the SDN 025 Teluk Binjai East Dumai subdistrict. Key Word : Model Cooperative Think Pair Share, The Study Result Of IPS Subject.